Perkembangan Arsitektur dan Fungsi Kelenteng Tjo Soe Kong di Tanjung Kait Tahun 1959-2018 - Baasila, Fillah Hania; Maryuni, Yuni; Wibowo, Tubagus Umar Syarif Hadi (LPPM Institut Nasional Laa Roiba Bogor, 2024)
This study aims to explain the history, development building form, and explain the function of Tjo Soe Kong Temple in Tanjung Kait. Historical methods used in research consisting heuristics, source criticism, interpretation, and historiography. The results showed that the establishment of the Tjo Soe Kong Temple was related Kongco Tjo Soe Kong to the expansion of sugarcane land. The construction was carried out by residents of Chinese descent were immigrants from Anxi district, in early decades of the 18th century to be precise in 1792, and has undergone several physical changes the building with addition of modern construction. First renovation in 1959, condition the building was made of wood, bamboo and blocks were replaced with bricks and cement to strengthen the building. Second renovation in 2018, namely repairing the roof, walls, poles, fences, and ornaments. As well as the structure of the wall construction is coated with granite which serves to add to the impression of beauty of the building without losing its original shape. Establishment of the Tjo Soe Kong Temple follows general rules of feng shui but not completely. The function of the temple building is use as a place of worship for Buddhists, center for social activities and assimilation of arts, historical marker of development of Chinese community, a place where spiritual teachings also used for recreation because it’s crowded with visitors and open to public. Addition of red bridge building with fish pond to enjoy the beautiful scenery at the Tjo Soe Kong Temple.